The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.1016/j.jprocont.2010.11.015
|View full text |Cite
|
Sign up to set email alerts
|

On the design of integral observers for unbiased output estimation in the presence of uncertainty

Abstract: Integral observers are useful tools for estimating the plant states in the presence of non-vanishing disturbances resulting from plant-model mismatch and exogenous disturbances. It is well known that these observers can eliminate bias in all states, given that as many independent measurements are available as there are independent sources of disturbance. In the most general case, the dimensionality of the disturbance vector affecting the plant states corresponds to the order of the system and thus all states n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Noise and uncertainty are not critical factors in such a context. This can be very different in the case of industrial processes, as shown in a recent study by Bodizs et al (2011), where the performances of observers using an ELO, EKF or integrated Kalman filters (IKFs) are compared. The influence of noise and uncertainty on these observer types was emphasized, with more reliable results produced by ELOs, which permit exact state reconstruction of highly perturbed systems.…”
Section: B Schwaller Et Almentioning
confidence: 99%
“…Noise and uncertainty are not critical factors in such a context. This can be very different in the case of industrial processes, as shown in a recent study by Bodizs et al (2011), where the performances of observers using an ELO, EKF or integrated Kalman filters (IKFs) are compared. The influence of noise and uncertainty on these observer types was emphasized, with more reliable results produced by ELOs, which permit exact state reconstruction of highly perturbed systems.…”
Section: B Schwaller Et Almentioning
confidence: 99%
“…Noise and uncertainty are not critical factors in such a context. This can be very different in the case of industrial processes, as shown in a recent study by Bodizs et al (2011), where the performances of observers using ELOs, EKFs or Integrated Kalman Filters (IKFs) are compared. The influence of noise and uncertainty on these observer types was emphasized, with more reliable results produced by ELOs, which permits the exact state reconstruction of highly perturbed systems.…”
Section: B Schwaller Et Almentioning
confidence: 99%
“…It comes from the form of the characteristic polynomial (8), in which the angular speed ω occurs only in even powers in this case.…”
Section: Parameter Selection Of the Pi Observermentioning
confidence: 99%
“…Another difficulty is the fact, that there exists a class of observed systems, for which the PI observer is always unstable, independently of its gains. The dependence of stability on the numbers of outputs and state variables is stated in [8]. The induction motor is the exemplary system that belongs to this class.…”
Section: Introductionmentioning
confidence: 99%